The German Capital Levy Tax: The National Emergency Tax Levy (Reichsnotopfer) (Quarterly Journal of Economics, 1920)
Appendix Get access The Quarterly Journal of Economics, Volume 34, Issue 3, May 1920, Pages 545–563, https://doi.org/10.2307/1883367 Published: 01 May 1920